Examining profit-sharing financing dynamics in Indonesian Islamic banking: ECM and ARDL approaches - Sandia, Sandi; Ascarya , Ascarya; Sulaeman, Sulaeman (Faculty of Economics, Universitas Islam Indonesia, 2025)
Purpose – This study examines the key factors driving profit-sharing financing growth in Indonesian Islamic banks and offers insights into post-Covid-19 recovery strategies.Methodology – This study used the ECM and ARDL methods to analyze short-term adjustments and long-term dynamics in 35 Indonesian Islamic banks. Findings – The results indicate that money supply, liquidity ratio, and financial profitability drive both short- and long-term growth in profit-sharing financing. Conversely, inflation and financial risk negatively affect the long-term expansion of such financing. Meanwhile, exchange rates, interest rates, and operational efficiency do not have a significant influence. Additionally, the findings highlight that long-term relationships in profit-sharing financing remain stable, with temporary short-term imbalances.Implications – This study provides evidence for policymakers and Islamic bank management to develop strategies to enhance profit-sharing financing, support Islamic banking growth, and guide post-Covid-19 recovery policies. Insights highlight key areas for strengthening Islamic banking operations in Indonesia.Originality – This study builds on previous research by applying the ECM and ARDL frameworks, providing a more comprehensive analysis of profit-sharing financing determinants in Indonesian Islamic banking.